The symbolic meaning of "Punakawan Javanese Wayang" (a value imaging study in character education at the character education course in STKIP Bina Insan Mandiri Surabaya) - Sulistiyani; Dewi Rosaria Indah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2019)
This study aims to examine the image of figures of clowns in Javanese puppetry in order to enhance the values ​​in character education of students in the world of education through symbolic meaning. This proves that education without character and character has been considered to fail to educate the nation's children. Many school graduates and scholars who are good at answering exam questions, have intelligent minds, but mentally weak, timid, and behavior is not commendable and do prohibited acts. With image theory and symbols in the puppet the author conducted an analysis to examine the image of the clown who then got the symbol of punokawan in Javanese wayang. This study uses interpretive descriptive methods and literature using image and symbol theory. The research used in this study has the purpose of understanding the phenomena experienced by the research subject. The results of this study can be formulated that the image of figures of Javanese puppets is symbolic, ie clowns in Javanese wayang as servants who have exemplary attitudes (honesty, fairness, not giving up / despair, and a high sense of nationalism) that are very necessary and implied in the value of character education. Character education in the subject of character education for students, especially students of STKIP Bina Insan Mandiri Surabaya, is more encouraging to be socialized to all academics so that they can create a generation that is of good quality in terms of intellectual, personality and character in the future.